Territorial Governance in Times of Crisis - Giovannini, Arianna. author. aut Link
XVII, 134 p. 10 illus.
Keywords: "The Covid19 pandemic contributed to shed light on the unresolved issues that have long underpinned Italian regionalism. This book re-constructs and assesses them from a multi-dimensional perspective, offering an original, rigorous and timely analysis of territorial governance dynamics that will be valuable also for other countries." —Gianfranco Viesti, Professor of Applied Economics, University of Bari, Italy. This book offers a comprehensive analysis of multi-level governance, political communication and public opinion in Italy during the Covid-19 pandemic. It demonstrates how the crisis acted as a catalyst in amplifying and exacerbating existing territorial disparities, while also highlighting the resilience and adaptability of some regions to cope with the emergency. The book also delves into the national and sub-national responses to the pandemic, examines how politicians and regional leaders presented them to the public, and how they were perceived by citizens. Through this analysis, it provides deeper insights into the intricate interplay between centralization and decentralization, as well as the diverse strategies employed by policymakers to address a wide spectrum of health, social, and economic challenges. Ultimately, by shifting the focus from institutions to citizens, the book reflects on how external shocks can both challenge the democratic underpinnings of decentralization and offer opportunities to strengthen them. These findings have important repercussions for many other nations, where debates over centralization and decentralization remain a pertinent and important issue. Arianna Giovannini is Associate Professor in Political Sociology in the Department of Economy, Society and Politics, University of Urbino Carlo Bo, Italy. Antonella Seddone is Associate Professor in Political Science in the Department of Cultures, Politics and Society, University of Turin, Italy. Davide Vampa is Senior Lecturer in Territorial Politics and co-director of the Centre on Constitutional Change, University of Edinburgh, UK.